Penerapan Model Usaha Keadilan Gender untuk Peningkatan Kesejahteraan Kelompok Wanita Tani di Bener Meriah - Mursyidin Mursyidin; Ainol Mardhiah; Herdian Saputra; Mustafa Kamal; Dedy Darmansyah; Fauzi Fauzi; Nur Hafni (Jurnal Pengabdian Masyarakat: Darma Bakti Teuku Umar, 2025)
This research was initiated to identify the issues faced by women farmers in Bener Meriah Regency which have been mostly experienced due to inequality of resources, training, and technology. This effort aims at establishing a gender equitable business model to enhance well-being of women farmers through the use of eco-friendly and sustainable technology. As one of the proposed solution is the using of greenhouse technology that integrated with solar panel in order to minimize problem of weather unreliable, especially during drying process in Arabica coffee bean. Furthermore, it also serves as a solution on the needs of on how of Bukit Diana Makmur Producers Cooperative with their Cavendish banana derivative product processing, by applying solar panels to inflate its ovens and stirrers in making biscuits. The study findings provide evidence to suggested that use of Green House and solar energy for chilling operations are beneficial in enhancing production efficiency, minimizing the requirement of conventional source of energy and increasing product capacity and quality. Facilitation of processing and agricultural production tools will enable increase of volume, improve positison in ther market and indirectly increased the income pf farmer group members to improve their welfare. The study recommends that sustainable technology should be adopted among women’s farmers in the area.